Bài tập  /  Bài đang cần trả lời

Tìm x

Giải các phương trình sau:
----- Nội dung ảnh -----
```
17) 1
---- + 2 = 5
2x - 2 3x + 3;

19) (x + 1) (x - 1) 2x
--------- + --------- = 0;
2x - 2 2x + 2

18) 1 1
---- - ---- = 4
6x - 2 3x - 1;

20) x x 2x
--------- + --------- = 0;
2(x - 3) 2x + 2 (x - 3)(x + 1)
```
2 Xem trả lời
Hỏi chi tiết
41
Tham khảo câu trả lời từ Trợ lý ảo Lazi
To solve the equations in the images, let's break them down step by step.

### 17)
\[
\frac{1}{2x-2} + \frac{2}{x+1} = \frac{5}{3x+3}
\]

**Step 1:** Find a common denominator. The common denominator is \((2x-2)(x+1)(3x+3)\).

**Step 2:** Multiply through by the common denominator to eliminate fractions.

**Step 3:** Simplify and solve the resulting equation.

### 18)
\[
\frac{1}{6x-2} - \frac{3}{3x-1} = \frac{4}{3x+1}
\]

**Step 1:** Identify the common denominator of all fractions involved.

**Step 2:** Multiply through by that common denominator.

**Step 3:** Simplify and solve for \(x\).

### 19)
\[
\frac{x+1}{2x-2} + \frac{x-1}{2x+2} = \frac{2x}{(1-x)(x+1)}
\]

**Step 1:** Again, find a common denominator.

**Step 2:** Multiply through by that common denominator.

**Step 3:** Simplify and solve the equation.

### 20)
\[
\frac{x}{2(x-3)} - \frac{x}{2x+2} = \frac{2x}{(x-3)(x+1)}
\]

**Step 1:** Identify a common denominator.

**Step 2:** Multiply through by that common denominator to clear fractions.

**Step 3:** Simplify and solve the equation.

### General Approach:
1. **Clear Fractions**: Multiply all terms by the common denominator.
2. **Rearrange Terms**: Move all terms to one side of the equation.
3. **Combine Like Terms**: Simplify the equation.
4. **Solve the Resulting Polynomial**: Use factoring, the quadratic formula, or numerical methods as needed.

If you're still having trouble, let me know, and I can provide assistance for solving a specific equation!
2
0
Trúc Nguyễn
04/10 20:25:29
+5đ tặng
20)
đkxđ: x#3 và -1:
x(x+1) +x(x-3)=2*2x
x^2+x+x^2-3x-4x=0
2x^2-6x=0
2x(x-3)=0
2x=0 hoặc x-3=0
x=0(tm) hoặc x=3(loại)
Vậy x=0.

Mở khóa để xem toàn bộ nội dung trả lời

(?)
Bạn đã đạt đến giới hạn của mình. Bằng cách Đăng ký tài khoản, bạn có thể xem toàn bộ nội dung trả lời
Cải thiện điểm số của bạn bằng cách đăng ký tài khoản Lazi.
Xem toàn bộ các câu trả lời, chat trực tiếp 1:1 với đội ngũ Gia sư Lazi bằng cách Đăng nhập tài khoản ngay bây giờ
Tôi đã có tài khoản? Đăng nhập
0
0
Quỳnh
04/10 20:27:09
+4đ tặng
x/2(x - 3)+x/2x + 2 = 2x/(x - 3)(x + 1)
=> x(x+1)+x(x - 3)=4x
=>x^2+x+x^2-3x=4x
=> 2x^2-6x=0
=> 2x(x-6)=0
=> 2x = 0 hoặc x - 6 = 0 
=> X = 0 hoặc x= 6

Bạn hỏi - Lazi trả lời

Bạn muốn biết điều gì?

GỬI CÂU HỎI
Học tập không giới hạn cùng học sinh cả nước và AI, sôi động, tích cực, trải nghiệm

Hôm nay bạn thế nào? Hãy nhấp vào một lựa chọn, nếu may mắn bạn sẽ được tặng 50.000 xu từ Lazi

Vui Buồn Bình thường
×
Trợ lý ảo Trợ lý ảo
×
Đấu trường tri thức | Lazi Quiz Challenge +500k
Gửi câu hỏi
×